Developing an Interactive E-Book on Statistics Based on a Realistic Mathematical Approach Assisted by The SIPDA Learning Management System - Prihatin Ningsih Sagala; Eri Widyastuti (International Journal on Emerging Mathematics Education, 2022)
The government policy in March 2020 regarding the application of online learning has significant changes in the learning process on campus. One of them is by changing teaching materials from textbooks to e-books, which is a must as a form of adjustment related to campus conditions that implement full online learning using LMS SIPDA. The objectives of this study are: (1) Producing an interactive e-book on basics statistics based on Realistic Mathematics assisted by the SIPDA LMS developed by using a valid and practical Kvisoft Flipbook Maker (2) To determine the effectiveness of the e-book Basics of Statistics in improving student problem-solving abilities. This type of research is Research and Development with the ADDIE development model, namely analysis, design, development, implementation, and evaluation. E-book development using the Kvisoft Flipbook Maker Application. The results of the e-book development at the needs analysis stage showed that 85% of students needed integrated learning media. SIPDA integrated e-books can increase student attendance and activities by 60%. At the product design stage, the e-book in the form of a word file is converted into a PDF file and then developed using Kvisoft Flipbook Maker by adding videos, images, and other files. The e-book is validated with a validity rate of 92% by material experts and 89% by media experts. The value of practicality is seen from two things, namely: (1) Questionnaire for responses from media experts and two practitioner lecturers, it was found that the e-book developed could be applied in the good category (3.92) and met the practical criteria (80%) used in the online learning era. (2) The student response questionnaire in a small group of 10 people obtained the category Good (3.96) and very practical (85%). The percentage of student response questionnaire results at the implementation stage of the SIPDA class showed a positive response of 87.6%. The effectiveness aspect is seen from the average individual learning completeness of 71.42 with classical completeness criteria obtained by 91. And the N-Gain score was 0.71 in high category.